Let's explore Venus - Orme, Helen; Orme, David, 1948 Mar. 1- (Tunbridge Wells, Kent : Ticktock Entertainment, 2007)
Photographs, illustrations, and simple text provide details about Venus including what it looks like, comparison to the earth, its weather patterns, and space missions to the planet.
Where is Venus? -- Planet facts -- The weather on Venus -- Global warming -- On the surface -- Finding Venus -- What can we see? -- Missions to Venus -- Venus discoveries -- New missions.
Includes index.
3-6.
Keywords: Venus (Planet) -- Juvenile literature; Venus (Planet); Venus (Planet)